The effect of oregano essential oil on microbial load and sensory attributes of dried meat - Hernández, Helga; Fraňková, Adéla; Sýkora, Tomáš; Klouček, Pavel; Kouřimská, Lenka; Kučerová, Iva; Banout, Jan (Journal of the science of food and agriculture, 2017)
BACKGROUND: Microbial load can be controlled using either synthetic or natural preservatives. Particular interest has been focused on the potential application of plant essential oils as safer additives for meat. However, there is no published research on the use of essential oils during the meat drying process. This study was focused on enhancing the meat drying process by using oregano essential oil (OEO) to inhibit the growth of bacteria and thus obtain a value-added dried meat product. The sensory response from assessors is presented. RESULTS: It was found that the application of OEO in meat was effective in inhibiting Salmonella enteritidis and Escherichia coli. After 6 h of drying at 55 °C, 2 mL (0.038 mL L-1 air) and 1.5 mL (0.028 mL L-1 air) of OEO were considered as the minimal inhibitory concentrations (MICs) against S. enteritidis and E. coli respectively. Samples treated with 0.75 mL of OEO were more attractive for consumption compared with the control; at a higher concentration of OEO, the sensory quality of the food was affected. CONCLUSION: A value-added dried meat product obtained by using OEO to enhance food safety received an acceptable sensory response from consumers. © 2016 Society of Chemical Industry.
Keywords: Oils, Volatile; konzervace potravin; chuť; Salmonella enteritidis; oleje rostlin; potravinářské přísady; zvířata; skot; Food Additives; Animals; lidé; dobromysl (rod); oregano essential oil; Food Preservation; oleje prchavé; Escherichia coli; microbial load; masné výrobky; kontaminace potravin; Plant Oils; Humans; Food Contamination; meat drying; meat sensory attribute; Cattle; Taste; Origanum; Meat Products